2017
DOI: 10.1245/s10434-016-5760-8
|View full text |Cite
|
Sign up to set email alerts
|

Fewer Reoperations After Lumpectomy for Breast Cancer with Neoadjuvant Rather than Adjuvant Chemotherapy: A Report from the National Cancer Database

Abstract: BackgroundReoperations occur frequently after initial lumpectomy for breast cancer. The authors hypothesized that the receipt of neoadjuvant chemotherapy (NAC) is associated with fewer reoperations.MethodsThe association between timing of chemotherapy and reoperation rates (ROR) after lumpectomy was investigated for patients with stages 1–3 breast cancer in the National Cancer Database (NCDB) from 2010 to 2013 by multivariable logistic regression modeling. Then propensity score-matching was performed.ResultsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…There were fewer reoperations in solo- and academic-practice surgeon settings compared with other settings, and rates were higher with lobular histology and multifocality. Tumor size also is fixed at patient presentation; however, in select eligible patients, NAC can be considered and is associated with fewer reoperations 35,36. Lastly, commercial insurance, compared with no or “other” insurance, was another fixed factor associated with higher rates.…”
Section: Discussionmentioning
confidence: 99%
“…There were fewer reoperations in solo- and academic-practice surgeon settings compared with other settings, and rates were higher with lobular histology and multifocality. Tumor size also is fixed at patient presentation; however, in select eligible patients, NAC can be considered and is associated with fewer reoperations 35,36. Lastly, commercial insurance, compared with no or “other” insurance, was another fixed factor associated with higher rates.…”
Section: Discussionmentioning
confidence: 99%
“…In disagreement with these findings, in 2017 Landercasper et al found women who received NAC before BCS were less likely to have reoperations. However, their study was based on a large cancer registry patient population not intended to capture surgical outcomes and represented a patient cohort before the 2014 ASO‐ASTRO‐ASCO margin consensus guideline 15 . Our results demonstrate women who received NAC had lower re‐excision rates.…”
Section: Discussionmentioning
confidence: 73%
“…It is interesting to note that the presence of DCIS at the pathologically close margin (as opposed to invasive cancer) correlated to an increased likelihood of re-excision (p = 0.018). Although this cohort predates the recent SSO-ASTRO-ASCO DCIS guidelines published in 2016, clinical practice mirrors these recommendations [ 17 ]. However, the recommendation of the panel for margin width for DCIS in association with an invasive cancer was to apply the ‘no tumor on ink’ guideline for invasive cancer as these lesions natural history typically mirrors that of invasive cancer more closely.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were also excluded if the diagnosis was made by excisional biopsy, if the initial operation was performed at an outside institution, if they had less than 60 days of follow-up. Patients receiving neoadjuvant chemotherapy were also excluded as preoperative systemic treatment has been shown to substantially decrease the need for re-excision [ 17 ].…”
Section: Methodsmentioning
confidence: 99%